THE SIGNIFICANCE OF MULTIPLE SATURATION POINTS IN THE CONTEXT OF POLYBARIC NEAR-FRACTIONAL MELTING - Asimow P.D.; Longhi J. (My University, 2004)
Experimental petrologists have successfully located basaltic liquid compositions parental to mid-ocean ridge basalt that are, within experimental resolution, multiply saturated with three-phase harzburgite or four-phase lherzolite assemblages on their liquidus at some elevated pressure. Such an experimental result is a necessary consequence of any paradigm in which erupted basalts derive from single-batch primary liquids that equilibrate with a mantle residue and undergo no subsequent magma mixing before differentiation and eruption. Here we investigate whether, conversely, such evidence of multiple saturation is sufficient to exclude dynamic melting models wherein increments of melt are mixed after segregation from residues, during melt transport or in magma chambers. Using two independent models of crystal–liquid equilibria to simulate polybaric near-fractional peridotite melting, we find that aggregate liquids from such melting processes can display near-intersections of liquidus surfaces too close to distinguish experimentally from exact multiple saturation points. Given uncertainties in glass compositions, fractionation corrections, experimental temperature and pressure conditions, and achievement of equilibrium, these results suggest that polybaric mixtures can in fact masquerade as mantle-equilibrated single-batch primary liquids. Multiple saturation points on the liquidus surfaces of primitive basalts do, however, preserve information about the average pressure of extraction of their constituent increments of liquid.